Blue Economy Policy Implementation and Its Ecological Implications in Tomini Bay - Podungge, Abdul Wahab; Solihin, Dwi Indah Yuliyani; Adipu, Yulianty; Aneta, Yanti (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
Industrial and mining activities around Tomini Bay have significantly impacted marine ecosystems. This study aims to analyze the formulation process of the blue economy policy using an institutional approach, which includes the structure and process of decision-making, the role of key actors, and the impact of norms, rules, and regulations on the policy. In addition, this study evaluates the policy from a sustainable ecosystem perspective. Employing a qualitative approach combined with a research-action model, this study focuses on collaboration between researchers and stakeholders to identify problems, develop solutions, and implement practical changes. Findings reveal that the blue economy in Tomini Bay has been poorly implemented, primarily due to the lack of collaboration among the government, the private sector, and communities. This has resulted in damage to marine biodiversity and conflicts between mining operations and marine resource management. Therefore, the blue economy must be implemented holistically, with sustainable planning and management as well as proper environmental impact mitigation. Policy formulation can be more effective if it focuses on four main aspects: development of marine industries such as fisheries and seaweed management, optimization of the shipbuilding industry, diversification of coastal tourism, and strengthening of maritime services for economic equality. This study is limited by its scope and level of participation, which restricts the extent to which the findings reflect the dynamics of the social and economic ecosystem of the region.